Assessment of the influence of gap wall mobility factor at calculation of leakage in working section of a scroll compressor. Part 1 - V. A. Pronin; A. V. Kovanov; V. A. Tsvetkov; E. N. Mikhailova; E. A. Kalashnikova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The scroll type compressor is widely used in the medium capacity segment of refrigeration and air conditioning technology including heat pumps. Today there is an active process of changing from hydrofluorocarbons to natural refrigerants with low global warming potential. CO2, with its low critical point and correspondingly high operating pressures, is gaining in importance. For operation with new refrigerants, the scroll compressor has to be adapted to take account of all its design features, the most important of which are the clearances in the machine's flow area. It has to be considered that the thermodynamic properties of carbon dioxide, different from hydrofluorocarbons, have a significant influence on the volume and energy values of the compressor. In this case relevance consists in increase of accuracy of compressor losses calculation and prediction of refrigeration machine characteristics. As the basic volumetric losses in the scroll compressor are leakages of working substance in its working part, and the process of flow of medium is unsteady, their quantitative component causes interest. The purpose of this work is to clarify the physical basis of the leakage process in the radial clearance and the degree of influence of various factors on it. Such analysis gives further opportunity to refine the methodology of calculation of leakages of compressed medium, taking into account the mobility factor of gap walls. It will raise accuracy of the received results which can serve as a base to prognosis of optimum characteristics of the compressor, due to their approximation and will allow to optimize designing of refrigerating machines at the chosen modes of work.